Perceived power dynamics in nursing education on students’ learning experience in Ghana - Collins Atta Poku; Veronica Adwoa Agyare; Samuel Baafi; Priscilla Yeye Adumoah Attafuah; Eunice Berchie (PLoS ONE, 2025)
Introduction Educator-student connectedness is where students can thrive, even amid failure, preserving their worth and self-dignity. Every relationship may have challenges, which is no different in nursing education. Students are sometimes unhappy with the educator-student relationship, as power creates a certain distance that must be appropriately exhibited. The study explored the perceived power dynamics of the educator-student relationship in nursing education. Methods The study utilised an exploratory, descriptive qualitative approach to understand student nurses’ educator-student interaction. Twenty-four final-year students were involved in the study based on information power. Thematic analysis was used to generate codes, sub-themes, and themes. Findings Two main themes emerged: 1) difficulties faced by students and 2) the perceived impact of power dynamics. The identified subthemes include issues with teaching methods, feelings of suppression, and discouraging attitudes of educators. The findings further showed that students often pretend to understand when an educator becomes angry, reflecting the power dynamics in the classroom, where students may feel powerless to challenge authority even when their academic needs are unmet. Additionally, there is a lack of student autonomy, which affects their mental well-being and development as competent professionals. Conclusion Students are expected to develop critical thinking skills and become advocates for their patients; however, when their voices are suppressed, it is unlikely that they will confidently advocate for others in clinical settings. Suppressing their concerns can lead to long-term consequences, affecting their ability to question clinical decisions and their willingness to speak up for patient safety. Educational institutions should provide professional development on creating inclusive and supportive classroom dynamics to mitigate the adverse effects of power imbalances.